Studies On The Parameters That Affect The Properties Of Triple Nickel Electroplating - Ooi , Chee Heng (2003)

(untitled)
The triple nickel electroplating consists of three layers of nickel deposits with different sulphur content, i.e. the first layer plated on the substrate is semi-bright, followed by high sulphur and bright nickel. This research is aimed at studying the parameters that affect the various properties of triple nickel deposits such as cathode current .. efficiency, thickness distribution, brightness and leveling, co-deposited sulphur content, electrode potential differences and the corrosion resistance performance. The parameters being studied are the distance between cathode and anode, current density, plating time and the combination of different layers of nickel deposits.